Bibliometric Analysis of Published Original Research Articles on Leisure Constraints between 1991 and 2019 - Kose, Elif; Yerlisu-Lapa, Tennur; Gokce, Huseyin; Alexandris, Kostas; Yucel, Ali Serdar (Iranian Scientific Society Medical Entomology, 2023)
Background: The decrease in the frequency and duration of participation in leisure activities has negative effects on the physical, cognitive and psychological health of individuals. In this context, identifying the obstacles, which prevent individuals from participating in leisure activities, may offer important clues to institutions and organizations in taking measures to increase participation.Methods: The bibliometric analysis method was used in this study. The research was carried out with 306 articles scanned from the Web of Science (WoS) core database between 1991 and 2019. Results: Studies conducted in leisure area increased systematically according to 5-year periods and mostly authors from USA, Australia and Canada produced them. The mainstream subjects, which attracted the attention of researchers during recent years, are detected to be self-efficacy, segmentation, mental health and fear related to intrapersonal constraint topics.Conclusion: In order to cope with physical and mental health problems resulting from aging of the world po-pulation, and technological developments, and negative effects generated by inactive modern life style, priority should be given to studies on leisure constraints to be conducted on a more comprehensive basis. Another suggestion is to encourage health policies and applications which can increase participation in leisure activities.
Keywords: Bibliometric analysis; Leisure constraints; Mental health; Physical activity; Public health